2022
DOI: 10.3389/fimmu.2022.1099535
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: Cutaneous kinase activity correlates with treatment outcomes following PI3K delta inhibition in mice with experimental pemphigoid diseases

Abstract: A Corrigendum onCutaneous kinase activity correlates with treatment outcomes following PI3K delta inhibition in mice with experimental pemphigoid diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In line with previous findings, methylprednisolone as another first-line therapy for MMP, was also able to reduce the severity of skin, although not oral lesions in this mouse model. In this study, Ghorbanalipoor et al also showed that parsaclisib, a selective inhibitor of phosphoinositide 3-kinase delta (PI3Kd) significantly reduced skin and oral mucosal lesions (99,100). With regard to the characteristic symptom of scarring, typically occurring at the eyes of anti-laminin 332 MMP patients, this mouse model may also be suitable to unravel signaling pathways that contributes to this specific immunopathogenesis.…”
Section: Pathophysiology Of Anti-laminin 332 Pemphigoidmentioning
confidence: 65%
“…In line with previous findings, methylprednisolone as another first-line therapy for MMP, was also able to reduce the severity of skin, although not oral lesions in this mouse model. In this study, Ghorbanalipoor et al also showed that parsaclisib, a selective inhibitor of phosphoinositide 3-kinase delta (PI3Kd) significantly reduced skin and oral mucosal lesions (99,100). With regard to the characteristic symptom of scarring, typically occurring at the eyes of anti-laminin 332 MMP patients, this mouse model may also be suitable to unravel signaling pathways that contributes to this specific immunopathogenesis.…”
Section: Pathophysiology Of Anti-laminin 332 Pemphigoidmentioning
confidence: 65%